Pengaruh Ukuran Perusahaan, Profitabilitas, Struktur Modal dan Struktur Aset Terhadap Nilai Perusahaan - Kurniawan, Ikhwan; Sihono, Agus (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to examine the effect of firm size, profitability, capital structure, and asset structure on firm value in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2019–2023 period. This causal research employs secondary data obtained from annual reports and applies purposive sampling, resulting in 13 companies with a total of 65 observations. Multiple linear regression analysis was conducted after passing classical assumption tests. The findings indicate that profitability and capital structure have a significant positive effect on firm value, while asset structure has a substantial adverse effect. Firm size shows no significant impact on firm value. These results suggest that efficiency has a greater influence on firm value in resource utilization and financial structure management than the size of assets owned. This study contributes to the corporate finance literature, particularly in the context of Indonesia’s food and beverage industry. It provides practical implications for managers and investors in making informed investment decisions.